Kewenangan Hakim Mengabulkan Isbat Nikah atas Perkawinan Siri Poliandri dalam Hukum Perkawinan - Syarifah Maryam Putri Husain; Saharuddin Saharuddin; Moh Alfatah Alti Putra; Putri Rezky Ananda Ilyas; Ferry Ferry; Alya Salsabila (Jurnal Litigasi Amsir, 2025)
This article examines the legal treatment of a poliandrous unregistered marriage within the Indonesian marriage law framework through a normative juridical analysis of Decision Number 531/Pdt.P/2021/PA.Pwl. The study focuses on how religious court judges apply the monogamy principle, as enshrined in the Marriage Law, the Compilation of Islamic Law, and relevant Islamic legal texts, when assessing a petition for isbat nikah filed by a woman who remains legally married to her first husband while entering into a subsequent siri marriage. Using a statute approach and case approach, the research analyses statutory provisions on marriage validity, marriage registration, prevention and annulment of marriage, and the legal consequences of fasid (defective) marriages for spouses and children. The findings highlight the doctrinal and practical boundaries of judicial authority in legalising unregistered marriages that conflict with monogamy and demonstrate how the courts reconcile protection of children’s civil rights with the non-recognition of the underlying poliandrous union